2018
DOI: 10.1108/md-06-2017-0561
|View full text |Cite
|
Sign up to set email alerts
|

The interactive impact of online word-of-mouth and review helpfulness on box office revenue

Abstract: Purpose While a number of studies examined the eWOM (online word-of-mouth) factors affecting box office, the studies on the impact of review helpfulness on box office are lacking. The purpose of this paper is to fill the void in previous studies and further extend prior work regarding eWOM and box office. In order to explain the interaction effect of helpfulness with other variables on product sales, this study posits that review characteristics such as number of reviews, review rating, review length interact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
60
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 70 publications
5
60
2
Order By: Relevance
“…From adverse selection and quality uncertainty frameworks [3][4][5], this paper utilizes consumers' reliance on eWOM as a reasonable behavior to reduce information asymmetry and uncertainty in e-commerce. On the basis of social engagement and social risk frameworks, eWOM variables such as valence (review rating) and volume can be understood as crucial factors to reduce social risk and information asymmetry affecting product sales [6], purchasing intentions or decisions [7,8], product imagery [9] or brand attitudes [10]. Further, the usefulness, or helpfulness, of online reviews has been considered to be important, as helpfulness can affect the relationship between eWOM and product sales [6,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From adverse selection and quality uncertainty frameworks [3][4][5], this paper utilizes consumers' reliance on eWOM as a reasonable behavior to reduce information asymmetry and uncertainty in e-commerce. On the basis of social engagement and social risk frameworks, eWOM variables such as valence (review rating) and volume can be understood as crucial factors to reduce social risk and information asymmetry affecting product sales [6], purchasing intentions or decisions [7,8], product imagery [9] or brand attitudes [10]. Further, the usefulness, or helpfulness, of online reviews has been considered to be important, as helpfulness can affect the relationship between eWOM and product sales [6,11].…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of social engagement and social risk frameworks, eWOM variables such as valence (review rating) and volume can be understood as crucial factors to reduce social risk and information asymmetry affecting product sales [6], purchasing intentions or decisions [7,8], product imagery [9] or brand attitudes [10]. Further, the usefulness, or helpfulness, of online reviews has been considered to be important, as helpfulness can affect the relationship between eWOM and product sales [6,11]. Helpful reviews provide review diagnosticity and a source of differentiation, resulting in greater potential value to customers [12].…”
Section: Introductionmentioning
confidence: 99%
“…The results of the principal component analysis showed that the timeliness of information was the influencing factor of high satisfaction (H. Chen & Qi, 2016). The quality of e-word-of-mouth information, which is characterized by timeliness, accuracy and information content has an impact on the perceived trust of e-word-of-mouth (S. Lee & Choeh, 2018). More research shows that customer satisfaction (Iglesias, Markovic, & Rialp, 2019)、trust (Tabrani, Amin, & Nizam, 2018) is an important factor of commitment (Lee & Wong, 2016).…”
Section: International Journal Of Human Resource Studiesmentioning
confidence: 98%
“…Although a number of studies have focused on the antecedents of ORH in both the information management [18,50,51,52,53,65,66,75] and marketing management [80,88,89,127] fields looking at what makes an OR helpful, only two studies have tried to analyze the impact of helpfulness on commercial performance [86,134]. Lee and Choeh [86] measure the interaction effects of OR volume and valence with ORH to observe the effects on movie box office and interestingly find that OR volume "does not interact with helpfulness to influence box office" [86, p. 860]. However, the explanation provided to interpret this finding looks not satisfactory, and we review it in more depth in the development of our hypotheses.…”
Section: Orh and Financial Performancementioning
confidence: 99%
“…The urgency of these calls for research on the commercial and financial effects of ORH in the hospitality sector is critical, as hotel customers increasingly use helpful ORs to make purchasing decisions [54], with some groups of consumers using them as a selective processing mechanism [55]. Moreover, while a few scholars have analyzed the direct effects of OR valence and volume on firm performance (e.g., [28,95,101,103,133,151]), to the best of our knowledge no study has yet examined if and to what extent ORH interacts with other OR features such as OR valence and volume in affecting (hotel) financial performance, except for two studies conducted on the movie sector [86,134] and examining products rather than services.…”
mentioning
confidence: 99%